Process Evaluation of Making HEPA Policy Practice: A Group Randomized Trial. Issue 5 (September 2016) - Weaver, Robert G.; Moore, Justin B.; Huberty, Jennifer; Freedman, Darcy; Turner-McGrievy, Brie; Beighle, Aaron; Ward, Diane; Pate, Russell; Saunders, Ruth; Brazendale, Keith; Chandler, Jessica; Ajja, Rahma; et al.
This study examines the link between implementation of Strategies to Enhance Practice (STEPs) and outcomes. Twenty after-school programs (ASPs) participated in an intervention to increase children's accumulation of 30 minutes/day of moderate to vigorous physical activity (MVPA) and quality of snacks served during program time. Outcomes were measured via accelerometer (MVPA) and direct observation (snacks). STEPs implementation data were collected via document review and direct observation. Based on implementation data, ASPs were divided into high/low implementers. Differences between high/low implementers' change in percentage of boys accumulating 30 minutes/day of MVPA were observed. There was no difference between high/low implementers for girls. Days fruits and/or vegetables and water were served increased in the high/low implementation groups, while desserts and sugar-sweetened beverages decreased. Effect sizes (ES) for the difference in changes between the high and low group ranged from low (ES = 0.16) to high (ES = 0.97). Higher levels of implementation led to increased MVPA for boys, whereas girls MVPA benefited from the intervention regardless of high/low implementation. ESs of the difference between high/low implementers indicate that increased implementation of STEPs increases days healthier snacks are served. Programs in the high-implementation group implemented a variety of STEPs strategies, suggesting local adoption/adaptation is key to implementation.